2022
DOI: 10.1021/acsami.1c24154
|View full text |Cite
|
Sign up to set email alerts
|

Smart Magnetotactic Bacteria Enable the Inhibition of Neuroblastoma under an Alternating Magnetic Field

Abstract: Magnetotactic bacteria are ubiquitous microorganisms in nature that synthesize intracellular magnetic nanoparticles called magnetosomes in a gene-controlled way and arrange them in chains. From in vitro to in vivo, we demonstrate that the intact body of Magnetospirillum magneticum AMB-1 has potential as a natural magnetic hyperthermia material for cancer therapy. Compared to chains of magnetosomes and individual magnetosomes, the entire AMB-1 cell exhibits superior heating capability under an alternating magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Therefore, AMB-1 not only can produce imaging signals for positioning and diagnosis without additional labelling, but also have therapeutic function. Similar to previous observations, [23][24][25][26][27][28] we demonstrated that AMB-1 can efficiently shorten the T 2 relaxation time of tumor tissue, generating T 2 contrast enhancement. In addition, AMB-1 can convert the alternating magnetic field (AMF) into heat for magnetic hyperthermia, showing high performance in the thermal ablation of solid tumors.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, AMB-1 not only can produce imaging signals for positioning and diagnosis without additional labelling, but also have therapeutic function. Similar to previous observations, [23][24][25][26][27][28] we demonstrated that AMB-1 can efficiently shorten the T 2 relaxation time of tumor tissue, generating T 2 contrast enhancement. In addition, AMB-1 can convert the alternating magnetic field (AMF) into heat for magnetic hyperthermia, showing high performance in the thermal ablation of solid tumors.…”
Section: Introductionsupporting
confidence: 91%
“…19,20 Despite the great progress in magnetosomes, the exploration of the whole magnetotactic bacteria for biomedical applications remains a challenge. Recently, it has been demonstrated that magnetotactic bacteria can migrate to hypoxic tumor areas under the guidance of an external magnetic field for delivering drug-containing nanoliposomes or photothermal agents, 21,22 or serve as MRI contrast and magnetic hyperthermia agents, [23][24][25][26][27][28] suggesting the potential of the entire magnetotactic bacteria for biomedical applications. Magnetotactic bacteria are a kind of facultative anaerobe, and the investigation of their hypoxia-driven targeting effects for efficient tumor treatment is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…28 They move along earth's magnetic field by producing magnetosome magnetite crystals. 29,30 Their innate magnetism allows them to swim farther than their body length per second and spontaneously form clusters, allowing for collective behaviors. 23,25 In addition, the high motility of MTB can be actuated by combining with an external magnetic field.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This special property arises due to the presence of one or several chains of magnetic nanoparticles coated with a lipid bilayer membrane, called magnetosomes. , The mineral core of these magnetosomes presents high chemical purity, being made of magnetite, Fe 3 O 4 , in most of the species, though some of them synthesize greigite, Fe 3 S 4 . The size of the magnetic crystals typically ranges between 35 and 120 nm, being magnetically stable at room temperature. , Magnetosomes also exhibit high crystallinity, biocompatibility, and magnetic response, thereby attracting great interest in different research areas, especially those related to cancer treatment and similar biomedical applications. − In addition, magnetosomes, due to their exceptional characteristics, have also been considered as ideal model systems of magnetic nanoparticles. − …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been growing interest in using not only the isolated magnetosomes but also the whole MTB as biomedical nanobio-robots, nanobiots , for different theranostic applications such as magnetic resonance imaging, magnetic particle imaging, drug delivery, magnetic hyperthermia, and so forth. ,,,− Seizing the advantage of the self-propulsion capability provided by their flagella and the presence of the magnetosome chain, these bacteria can be guided and manipulated by external magnetic fields toward specific areas inside the human body. On top of that, MTB, due to their preference for low oxygen concentration environments, are naturally attracted toward hypoxic areas, such as tumor regions .…”
Section: Introductionmentioning
confidence: 99%